The dominance of introspective measures and what this implies: The example of environmental attitude - Siegmar Otto; Ulf Kröhne; David Richter (PLOS ONE, 2018)
The behavioral sciences, including most of psychology, seek to explain and predict behavior with the help of theories and models that involve concepts (e.g., attitudes) that are subsequently translated into measures. Currently, some subdisciplines such as social psychology focus almost exclusively on measures that demand reflection or even introspection when administered to persons. We argue that such a focus hinders progress in explaining behavior. One major reason is that such an exclusive focus on reflections results in common method bias, which then produces spurious relations, or in other words, low discriminant validity. Without the valid measurement of theoretical concepts, theoretical assumptions cannot be tested, and hence, theory development will be hampered. We argue that the use of a greater variety of methods would reduce these problems and would in turn foster theory building. Using a representative sample of N = 472 participants (age: M = 51.0, SD = 17.7; 54% female), we compared the validity of a classical introspective attitude measure (i.e., the New Ecological Paradigm) with that of an alternative attitude measure (i.e., the General Ecological Behavior scale). The latter measure, which was based on self-reported behavior, showed substantially better validity that we argue could aid theory development.
Keywords: 330